2005
DOI: 10.4049/jimmunol.174.8.4828
|View full text |Cite
|
Sign up to set email alerts
|

Intraepithelial Cell Neutralization of HIV-1 Replication by IgA

Abstract: HIV is transmitted sexually through mucosal surfaces where IgA Abs are the first line of immune defense. In this study, we used paired IgA and IgG mAbs against HIV gp160 to study intraepithelial cell neutralization and inhibition of HIV replication. African green monkey kidney cells, Vero C1008, polarizable epithelial cells transfected to express the polymeric Ig receptor (pIgR), were transfected with HIV proviral DNA, and intracellular neutralization mediated by the mAbs was assessed. D47A and D19A IgA, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 56 publications
2
44
0
Order By: Relevance
“…27,28 In addition to the role of IgG, several studies have also reported the importance of IgA against HIV. IgA has proven to be functional in protecting against HIV infection by direct neutralization, 29 -34 by inhibiting transcytosis of HIV across the mucosa, 29,31,35 -40 by intracellular virus neutralization, 41,42 and by preventing HIV entry past the epithelial lumen. 37 Furthermore, virus-specific IgA has been independently identified in the serum and cervicovaginal lavage of exposed uninfected (EU) cohorts of European, African, and Asian origins.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 In addition to the role of IgG, several studies have also reported the importance of IgA against HIV. IgA has proven to be functional in protecting against HIV infection by direct neutralization, 29 -34 by inhibiting transcytosis of HIV across the mucosa, 29,31,35 -40 by intracellular virus neutralization, 41,42 and by preventing HIV entry past the epithelial lumen. 37 Furthermore, virus-specific IgA has been independently identified in the serum and cervicovaginal lavage of exposed uninfected (EU) cohorts of European, African, and Asian origins.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases where intracellular neutralization by IgA has been described, for human immunodeficiency virus (HIV) (2,22), Sendai virus (18), and influenza virus (29), the active IgA molecule was directed at a viral protein known to be the target of extracellularly acting neutralizing antibodies. However, in the case of RV, such neutralizing antibodies directed to VP4 (44) did not exhibit intracellular neutralization activity.…”
Section: Discussionmentioning
confidence: 99%
“…The differential biologies of the Ser 248 -Fc␣RI and Gly 248 -Fc␣RI alleles could also play a role in other phenotypes involving IgA, including dermatitis herpetiformis, celiac disease, periodontal disease, and possibly IgA nephropathy. Even the uptake and inactivation of virus, demonstrated in epithelial cells with anti-HIV IgA, might be impacted by CD89 alleles (54). Because mice do not have FCAR, the gene encoding CD89, clues will not be forthcoming from studies of spontaneous mouse phenotypes but will need to be done in humans or, possibly, in mice reconstituted with human immune systems (55,56).…”
Section: The Ser 248 and Gly 248 Alleles Of Fc␣ri Affect Receptor Medmentioning
confidence: 99%